2008
DOI: 10.11646/zootaxa.1767.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A review of Aphidius Nees (Hymenoptera: Braconidae: Aphidiinae) in Iran: host associations, distribution and taxonomic notes

Abstract: A survey of aphid parasitoids belonging to Aphidius Nees was conducted in several parts of Iran, and 17 species were identified between 2001 and 2005. Parasitoids were reared from field-collected aphids, and the tritrophic associations of parasitoids, their aphid hosts, and the respective food plants were determined. The species of Aphidius parasitoids are listed with their distribution and aphid-plant associations. An illustrated key for species identification is presented. Ambiguity of some characters is dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 16 publications
0
35
0
3
Order By: Relevance
“…Although we detected statistically significant differences in the forewing shape and wing-venation pattern, some overlap is evident. The variability of the taxonomic characters commonly used in distinguishing these species (Starý, 1972, 1973, 1975; Pennacchio, 1989; Takada, 1998; Kavallieratos & Lykouressis, 1999; Tomanović et al ., 2003; Kavallieratos et al ., 2008; Rakhshani et al ., 2008), such as the number of antennal segments and the forewing venation pattern, led to a long list of synomizations within the A. colemani group (Starý, 1975). Differences in the shape of the forewing investigated within the biotypes of the A. colemani group are congruent with their genetic diversification on the basis of the barcoding region of mtCOI.…”
Section: Discussionmentioning
confidence: 99%
“…Although we detected statistically significant differences in the forewing shape and wing-venation pattern, some overlap is evident. The variability of the taxonomic characters commonly used in distinguishing these species (Starý, 1972, 1973, 1975; Pennacchio, 1989; Takada, 1998; Kavallieratos & Lykouressis, 1999; Tomanović et al ., 2003; Kavallieratos et al ., 2008; Rakhshani et al ., 2008), such as the number of antennal segments and the forewing venation pattern, led to a long list of synomizations within the A. colemani group (Starý, 1975). Differences in the shape of the forewing investigated within the biotypes of the A. colemani group are congruent with their genetic diversification on the basis of the barcoding region of mtCOI.…”
Section: Discussionmentioning
confidence: 99%
“…Rakhshani et al (2015) found 16 aphidiine species in Malta. Within Iran, Rakhshani et al (2008a) identified 17 species of Aphidius between 2001 and 2005. Olmez and Ulusoy (2003) found 16 species of aphid parasitoids between 1998 and 2000 within the Diyarbakir Province, Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…A. colemani is a common parasitoid of different aphids in Iran (Rakhshani et al 2008b,c) and other countries (Starý 1975; Kavallieratos et al 2004, 2010), but its taxonomic status is still considered problematic, due to character overlap with A. transcaspicus (Mescheloff and Rosen 1990; Takada 1998; Kavallieratos and Lykouressis 1999). The host range pattern is supposed to be the important biological border between the two related species.…”
Section: Discussionmentioning
confidence: 99%